The Effect of Compensation on the Performance of PT Employees. Global Paracation - Ismail (Journal GoodWill, 2022)
Technological developments have brought significant changes to various aspects of life, including the world of work and organizational structures. Humans are a key element in supporting this change, requiring companies to have human resources who are ready to keep up with technological developments. Employees, as a dynamic element in an organization, require special attention in order to continue to develop. Compensation, as a form of reward received by employees, has a crucial role in improving performance and motivation. A company's focus on fair and rational compensation arrangements is very important, because employee perceptions of inadequate compensation can reduce motivation and job satisfaction. This research focuses on the influence of compensation on employee performance at PT Global Parakasi. The research method involves collecting data through literature studies and field surveys using questionnaires and observations. Compensation analysis and simple linear regression are used to examine the relationship between compensation and employee performance. The results show that compensation has a positive and significant influence on employee performance, with 89.6% of the variation in performance can be explained by compensation. This conclusion is supported by the results of the simultaneous test (F-test) and partial test (t-test) which show that the regression model is valid for predicting employee performance.